Portal Vein Stenting Combined with 125I Particle Chain Implantation Followed by As2O3 in the Treatment of Hepatocellular Carcinoma with Portal Vein Tumour Thrombus. (31st January 2020) - Li, Zhaonan; Si, Guangyan; Jiao, De-Chao; Han, Xinwei; Zhang, Wenguang; Li, Yahua; Zhou, Xueliang; Liu, Juanfang; Chen, Jianjian
Abstract : Objective . To evaluate the feasibility and safety of portal vein stenting (PVS) combined with 125 I particle chain implantation and sequential arsenic trioxide (As2 O3 ) for the treatment of hepatocellular carcinoma (HCC) with portal vein tumour thrombus (PVTT) by transcatheter arterial chemoembolization (TACE). Methods . From January 2015 to January 2018, the clinical data of 30 patients with HCC complicated by PVTT were retrospectively analysed (26 men and 4 women). The laboratory examinations, incidence of adverse events, cumulative survival rate, and stent patency were analysed for all enrolled patients. Results . The success rate of interventional treatment in all patients was 100%. The results of the laboratory tests before and 1 week after surgery showed that the mean concentrations of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) decreased from 50.9 U/L ± 25.8 to 41.8 U/L ± 21.6 (P < 0.001 ) and 57.6 U/L ± 19.9 to 44.2 U/L ± 26.1 (P < 0.001 ), respectively. No complications in grade 3 or higher according to the Common Terminology Criteria for Adverse Events (CTCAE) were observed. The cumulative survival rates at 3, 6, 9, and 12 months were 83.1%, 69.2%, 43.7%, and 31.2%, respectively, while the patency rates of the stents were 83.3%, 80.0%, 52.2%, and 38.3%, respectively. Of the 30 deaths during the follow-up period, 16 patients died of liver failure, 8 died of gastrointestinal bleeding, 3 died of lung metastasis, 2 died of brain metastases, and 1 died of heart failure because the tumour invaded the atria. Conclusion . PVS combined with 125 I particle chain implantation followed by TACE with As2 O3 is safe and feasible for patients with PVTT. The long-term efficacy of this treatment needs to be further studied.